2010
DOI: 10.1371/journal.pone.0013288
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in Oxygen Sensing Define Early and Late Onset Preeclampsia as Distinct Pathologies

Abstract: BackgroundThe pathogenesis of preeclampsia, a serious pregnancy disorder, is still elusive and its treatment empirical. Hypoxia Inducible Factor-1 (HIF-1) is crucial for placental development and early detection of aberrant regulatory mechanisms of HIF-1 could impact on the diagnosis and management of preeclampsia. HIF-1α stability is controlled by O2-sensing enzymes including prolyl hydroxylases (PHDs), Factor Inhibiting HIF (FIH), and E3 ligases Seven In Absentia Homologues (SIAHs). Here we investigated earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 71 publications
6
93
1
Order By: Relevance
“…We have previously reported that aberrant oxygen sensing mediated by PHDs is a defining feature of E-PE (26). Hence, we examined JMJD6 expression in human placentae from E-PE and L-PE.…”
Section: Jmjd6 Is Elevated In Severe E-pe Placentaementioning
confidence: 99%
“…We have previously reported that aberrant oxygen sensing mediated by PHDs is a defining feature of E-PE (26). Hence, we examined JMJD6 expression in human placentae from E-PE and L-PE.…”
Section: Jmjd6 Is Elevated In Severe E-pe Placentaementioning
confidence: 99%
“…It is now apparent from studies into pregnancy-induced preeclampsia that both the severity of the disease and the birth outcomes are dependent on whether maternal complications commence in early or late pregnancy [27,28]. A comparable situation may also occur with regard to potential adverse effects of maternal obesity as well as gestational diabetes (irrespective of maternal body weight before pregnancy).…”
Section: How Do Maternal Obesity and Diet Influence The Early Nutritimentioning
confidence: 99%
“…Another 10 blood experimental biomarkers (AT-1AA [31], calcyclin, copeptin [34], galectin-1 [36], Gas6 [37], HIF-1aOH [38], IGFALS [41], mammalian HtrA3 [45], NT-proBNP [47], and PTX3 [49]), and four urine ones (C5b-9 [33], nephrin [46], iodine [42], and prolactin [52]) had limited clinical evaluation information, which impeded the evaluation of their performance for the diagnosis of PE. No clinical data were found for the remaining nine blood markers, which consisted of adipsin, α enolase, ADMA, Ba, 2,3-BPGM, Fetal DNA, marinobufagenin, plasma UA [51], and soluble CD117.…”
Section: Resultsmentioning
confidence: 99%